Pelatihan Pembuatan Website dan Pengelolaan Media Sosial Untuk Promosi Produk Lokal - Cep Lukman Rohmat; Dadang Sudrajat; Saeful Amri; Selvi Andini (CV. Multi Kreasi Media, 2022)
Improving the competitiveness of local products in the digital era requires micro, small, and medium enterprises (MSMEs) to be able to utilize information technology in their marketing processes. However, many local business actors still rely on conventional promotional methods and have not yet optimized the use of digital media. This Community Service Program (PKM) aims to assist partner MSMEs in increasing their product visibility through website creation and social media management as promotional tools. The program was carried out in several stages: identifying partner needs, training in the creation and management of websites using WordPress, training in content design and marketing strategies via social media (Instagram, Facebook, and WhatsApp Business), and mentoring in content creation and account management. During the program, partners were equipped with basic skills to build a simple online store website, copywriting techniques, product photography using smartphones, and the use of free design tools such as Canva. The results of the activity show that partners who previously had no online presence now have active websites displaying product catalogs, business profiles, and contact information. In addition, the partners’ social media accounts became more active and strategically managed, featuring consistent and engaging promotional content. This activity also increased partners’ understanding of the importance of digital identity and content-based marketing strategies. The PKM provided direct impact in the form of increased consumer trust in local brands, enhanced sales potential, and better preparedness of MSMEs to compete in the digital market. Moving forward, this training can be replicated in various local business communities as part of a technology-based community economic empowerment effort.